CELTIC SETTLEMENT GALISH-LOVACHKA IN THE TRANS-CARPATHIAN REGION: RECONSIDERATION OF CONTEXT (City: History, Culture, Society, 2023)
The settlement on the Galish and Lovachka hills near the modern Ukrainian city of Mukacheve is one of the most significant La Tène sites in the Upper Tisza region. From 1844 to 1930, amateur archaeologists unearthed the Galish-Lovachka site in an unsystematic manner. They uncovered twenty-four 18 structures, including dwellings and workshops, as well as several inhumation burials and approximately one thousand artifacts, such as iron tools, pottery vessels, bronze ornaments, weapons, and military equipment, etc. The majority of the inventory is from the LT B2-C period. The majority of the cultural layer of the Galish-Lovachka site was destroyed by plowing in the early twentieth century. Additional research conducted between 1962 and 1964 proved fruitless. On the Lovachka hill, archaeologists from Uzhhorod State University excavated multiple storage pits and a half-dugout dwelling between 1986 and 1989. The cultural layer contained fragments of wheel-made pottery and several metal objects. It is evident that Galish-Lovachka was an important metallurgy and ironworking center that engaged in long-distance commerce. Galish-Lovachka was also a political center of the surrounding area, as evidenced by the discovery of a number of artifacts indicating the high social status of their owners. The swords, which include a short sword with an X-shaped handle, iron chain belts for hanging a sword, horse bits, and chariot fittings from Galish-Lovachka, provide evidence for the presence of the Celtic military elite at the settlement. Few dozens of silver coins (primarily imitations of Philip II and Audoleon) were discovered in the settlement’s cultural layer. The discovery of a coin mold indicates that at least some local coins were produced. If Galish-Lovachka had become an oppidum, its well-developed crafts, coin minting, and high-status objects would indicate a certain stage in the evolution of La Tène settlements, but it did not. Galish-Lovachka is compared to well-known Central European Celtic sites such as Roseldorf, Nmice, and Nowa Cerekwa by the author. One may conclude that Galish-Lovachka was a typical Celtic “industrial village” of the middle La Tène period – a large rural settlement that served as the regional political and economic hub.
Keywords: Celts; La Tène; Galish-Lovachka; Trans-Carpathian region; early urban settlement; industrial village